Traditional Food serves in Wedding Ceremony As Cultur in Nagari Balah Aie Kabupaten Padang Pariaman - Riana Dwi Putri (Journal FAME: Journal Food and Beverage, Product and Services, Accomodation Industry, Entertainment Services, 2021)
This study purpose is to describe the implementation of the Manjalang Mintuo custom event, to identify the type of traditional food of Juadah, to describe the equipment used to bring the traditional food of Juadah and to express the meaning of the customary food brought to Manjalang Mintuo event.This research is a qualitative study with a descriptive approach, research location in Nagari Balah Aie District VII Koto Sungai Sariak Padang Pariaman. The object of research is a series of ceremonies of traditional wedding ceremonies, indigenous foods brought, tools used to bring custom food, and the meaning of custom food brought on the implementation of the ceremony Manjalang Mintuo. Data collection techniques with observation, interview and documentation. Data analysis techniques are data reduction, data presentation and conclusion.The results of this study indicate that (1)Manjalang Mintuo event series has two stages: first, preparation before the event consisting of processing and preparation of traditional food Juadah, and second, the implementation of Manjalang Mintuo consisting of jalan basamo, makan basamo, panyiriahan, pembukaan juadah  and, pulang ka rumah. (2)Traditional food at manjalang mintuo event is nasi kunyik, singgang ayam, juadah (wajik simanih, cake stamp/aluo,kanji, jalabio, kipang, juadah tuku/ambuik-ambuik, pinyaram). (3)Processing equipment and carrying custom food at the mintuo manjalang event is a kuali besar, kuali sedang, langsang, cetakan jalabio, cetakan ambuik-ambuik, sudu kayu/sudu basi, rumah-rumah tabui, tuduang samba, rendo, dalamak. 4)Traditional food at a ceremony Manjalang Mintuo has the meaning of household life and shows the silahturrahmi relationship between anak daro family and marapulai family. This research can make juadah as one of the culture heritage from Balah Aie VII Koto Sungai Sariak.Keywords: traditional food, wedding ceremony.